PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN MENYIMAK DONGENG DI ERA DIGITAL - Nurani, Riga Zahara; Nugraha, Fajar; Sidik, Geri Syahril (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2018)
Abstract: Learning in the 21st century is inseparable from the influence of digital technology. Learning listening of fairy tale with conventional method (teachers read a fairy tale in front of the class) is no longer suitable to be applied for the students in this digital era, so that a new breakthrough in the use of learning media is needed. Learning listening of fairy tale by using an audio visual media can be one of alternatives used by teachers. Research used an audio visual media in learning listening of fairy tale was conducted in SDN 6 Singaparna. Research method used is descriptive qualitative method. The enthusiasm of students in learning listening of fairy tale by using audio visual media is better than learning listening of fairy tale read by the teacher. This is seen from the average score of listening ability of student’s fairy tales. The average listening ability of student’s fairy tale using audio visual media is 84,53, while the average listening ability of student’s fairy tale before the research  was 67,20. In addition to making the average listening ability of student’s fairy tale increased was by the use of audio visual media that also made students more active in the learning process. This is seen when the teacher asked a few questions when the fairy tale has been played, most students responded well to the questions given by the teacher. Abstrak: Pembelajaran di abad ke-21 ini tidak terlepas dari pengaruh teknologi digital. Pembelajaran menyimak dongeng dengan cara konvensional (guru membacakan dongeng di depan kelas) dirasa sudah tidak cocok lagi diterapkan pada siswa di era digital ini, sehingga diperlukan adanya terobosan baru dalam penggunaan media pembelajaran. Pembelajaran menyimak dongeng dengan menggunakan media audio visual dapat menjadi salah satu alternatif yang bisa digunakan oleh guru. Penelitian tentang penggunaan media audio visual dalam pembelajaran menyimak dongeng dilakukan di SDN 6 Singaparna. Metode penelitian yang digunakan adalah metode deskriptif kualitatif.  Antusiasme siswa dalam pembelajaran menyimak dongeng dengan menggunakan media audio visual lebih baik daripada pembelajaran menyimak dongeng yang dibacakan langsung oleh gurunya. Hal ini terlihat dari rata-rata kemampuan menyimak dongeng siswa. Rata-rata kemampuan menyimak dongeng siswa setelah menggunakan media audio visual adalah 84,53, sedangkan rata-rata kemampuan menyimak dongeng sebelumnya hanya 67,20. Selain membuat rata-rata kemampuan menyimak dongeng siswa meningkat, penggunaan media audio visual juga membuat siswa lebih aktif dalam proses pembelajaran. Hal ini terlihat saat guru mengajukan beberapa pertanyaan saat dongeng telah diputar, sebagian besar siswa merespon dengan baik pertanyaan-pertanyaan yang diberikan oleh guru.